2012
DOI: 10.1016/j.bbalip.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Minimally modified LDL upregulates endothelin type B receptors in rat coronary artery via ERK1/2 MAPK and NF-κB pathways

Abstract: Minimally modified low density lipoprotein (mmLDL) is a well-known risk factor for coronary artery disease. Upregulation of vascular endothelin type B (ET B ) receptors on the vascular smooth muscle cells is predicted to be the molecular mechanism that leads to cardiovascular pathogenesis. The objective of the present study was to examine the hypothesis that mmLDL upregulates ET B receptors in rat coronary artery. The contractile responses to sarafotoxin 6c (ET B receptor agonist) were studied using a sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…It acts on two types of G protein-coupled receptors named the The upregulation of vasoconstrictive ET B receptor expression with increased vasoconstriction are seen in coronary artery infarction (Wackenfors et al, 2004) and experimental ischemic stroke (Stenman et al, 2002). This increased vasoconstrictive ET B receptor-mediated vasoconstriction are also found in the arterial segments treated with the risk factors such as cigarette smoke particles (Xu et al, 2008) or minimally modified low density lipoprotein (mmLDL) (Jie et al, 2012;Li et al, 2012). Blockage of extracellular signal-regulated kinases 1 and 2 (ERK1/2) mitogen-activated protein kinase (MAPK) signal pathways using Raf inhibitors has demonstrated that in cigarette smoke-exposed rats and in rat experimental subarachnoid hemorrhage model (Ansar et al, 2011), the upregulation of vasoconstrictive ET B receptor expression is associated with activation of Raf/ERK/MAPK signal pathways.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…It acts on two types of G protein-coupled receptors named the The upregulation of vasoconstrictive ET B receptor expression with increased vasoconstriction are seen in coronary artery infarction (Wackenfors et al, 2004) and experimental ischemic stroke (Stenman et al, 2002). This increased vasoconstrictive ET B receptor-mediated vasoconstriction are also found in the arterial segments treated with the risk factors such as cigarette smoke particles (Xu et al, 2008) or minimally modified low density lipoprotein (mmLDL) (Jie et al, 2012;Li et al, 2012). Blockage of extracellular signal-regulated kinases 1 and 2 (ERK1/2) mitogen-activated protein kinase (MAPK) signal pathways using Raf inhibitors has demonstrated that in cigarette smoke-exposed rats and in rat experimental subarachnoid hemorrhage model (Ansar et al, 2011), the upregulation of vasoconstrictive ET B receptor expression is associated with activation of Raf/ERK/MAPK signal pathways.…”
Section: Introductionmentioning
confidence: 97%
“…Taken all together, this suggests although mmLDL is still recognized by LDL receptor (Berliner et al, 1990), it has different effects from LDL on regulation of vasoconstrictive ET B and ET A receptor expressions in the arterial smooth muscle cells. One explanation for the lack effects of LDL at concentration of 2.2 mg protein/L (Jie et al, 2012;Li et al, 2013a;Li et al, 2012) is due to far low concentration of LDL used in the experiments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations